Macromolecular crowding in animal component-free, xeno-free and foetal bovine serum media for human bone marrow mesenchymal stromal cell expansion and differentiation - Korntner, Stefanie H.; Di Nubila, Alessia; Gaspar, Diana; Zeugolis, Dimitrios I. (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Cell culture media containing undefined animal-derived components and prolonged in vitro culture periods in the absence of native extracellular matrix result in phenotypic drift of human bone marrow stromal cells (hBMSCs). Methods: Herein, we assessed whether animal component-free (ACF) or xeno-free (XF) media formulations maintain hBMSC phenotypic characteristics more effectively than foetal bovine serum (FBS)-based media. In addition, we assessed whether tissue-specific extracellular matrix, induced via macromolecular crowding (MMC) during expansion and/or differentiation, can more tightly control hBMSC fate. Results: Cells expanded in animal component-free media showed overall the highest phenotype maintenance, as judged by cluster of differentiation expression analysis. Contrary to FBS media, ACF and XF media increased cellularity over time in culture, as measured by total DNA concentration. While MMC with Ficoll™ increased collagen deposition of cells in FBS media, FBS media induced significantly lower collagen synthesis and/or deposition than the ACF and XF media. Cells expanded in FBS media showed higher adipogenic differentiation than ACF and XF media, which was augmented by MMC with Ficoll™ during expansion. Similarly, Ficoll™ crowding also increased chondrogenic differentiation. Of note, donor-to-donor variability was observed for collagen type I deposition and trilineage differentiation capacity of hBMSCs. Conclusion: Collectively, our data indicate that appropriate screening of donors, media and supplements, in this case MMC agent, should be conducted for the development of clinically relevant hBMSC medicines.